Tre variazioni senza tema intorno a Proust e Beethoven (Itinera, 2024)
Proust’s Recherche has been, and still is, an inexhaustible source of inspiration for literary and philosophical studies. This essay aims to outline the network of relationships, some- times unexpected, that emerged from the intellectual environment of these studies, especially around the BCDEs, and their mutual influences from and on other fields of human thought and arts, even beyond the boundaries of literature and philosophy. A specific case study will be considered: a monographic issue of the French magazine L’Arc published in BCDE and dedicated to the bicentenary of Beethoven’s birth. We will first focus on the analysis of Beethoven’s Diabelli Variations by André Boucourechliev, which Roland Barthes compares to the narrative structure of the Recherche. Then, through an article by Barthes himself, Musica Practica, the approach to the interpretation of Beethoven’s works will be compared to the role of Proustian criticism. Here, Barthes also highlights the importance of amateur musical practice in understanding the very essence of a musical work. Finally, Igor Stravinsky’s commentary on Beethoven’s late string quartets will be related to Proust’s reflections on the modernity of the work of art.
Keywords: Proust, Beethoven, Variation, Amateur